Development and performance evaluation of a linear actuator based Wwarable assistive device - Makhdoomi , Mohatashem R.; Ba hamid, Alala M.; Saleh, Tanveer (2015)
For an assistive device to be usable in carrying out activities of daily living, it is highly important that the device be compact, light in weight and portable. It is even more important that the device be comfortable and safe to use. As different people have different hand sizes, the assistive hands must be designed considering the variety of hand sizes that can be accommodated without any compromise in safety or comfort. This can be best achieved by making use of a joint-less structure that takes the shape of the hand that wears it. This paper proposes the design of an assistive device that is lightweight, compact, safe and comfortable. This device assists the hand in gripping objects used in daily life activities. The performance evaluation of this device is carried out by measuring the gripforce exerted by the finger-tip on the object. The maximum range of grip-force exerted by this assistive hand is between 2.5 to 4.5 N. The minimum grip-force that can be applied is 0.9 N. The experiments conducted show the viability of the assistive device.